Human and material resources availability and utilization as correlates of students’ achievements in secondary school Yoruba language (2016)
The study evaluated the availability and utilization of human and teaching-learning materials as correlates of students' achievements in secondary school Yoruba language. The sample size consisted of 50 Yoruba language teachers schools were selected through multi-stage sampling technique. Three research questions guided the study with three valid and reliable instruments namely: Yoruba language Achievement Test (r =075); Yoruba Language Teachers Resource Utilization Observation Scale (r = 075); and Level of Availability of Materials and Human Resources Checklist (r =. 083). The data collected were analyzed using frequency count, percentage and descriptive statistics multiple regression. The study revealed that many public schools are poorly staffed and poorly structured with little or no material resources availability which negatively affect teaching and learning of Yoruba Language in Nigeria secondary schools. The paper was concluded with recommendation that government should make human resources available in schools. Materials resources should be provided by government, for teachers and students to facilitate effective teaching-learning of Yoruba language in Nigeria schools.